New Strait Times , 9 May 2010 - Syed Nadzri (The New Straits Times Press (M) Bhd, 2010)
Malaysians look destined to go down in history as grat, probably campulsive, road builders. And the news last week taht another highway is in the works to link the northern and southern parts of Peninsular Malaysia has certainly strengthened that prospect.